Normology: Integrating insights about social norms to understand cultural dynamics - Morris, Michael W.; Hong, Ying-yi; Chiu, Chi-yue; Liu, Zhi (Organizational behavior and human decision processes, 2015)
This paper integrates social norm constructs from different disciplines into an integrated model. Norms exist in the objective social environment in the form of behavioral regularities, patterns of sanctioning, and institutionalized practices and rules. They exist subjectively in perceived descriptive norms, perceived injunctive norms, and personal norms. We also distil and delineate three classic theories of why people adhere to norms: internalization, social identity, and rational choice. Additionally, we articulate an emerging theory of how perceived descriptive and injunctive norms function as two distinct navigational devices that guide thoughts and behavior in different ways, which we term “social autopilot” and “social radar.” For each type of norms, we suggest how it may help to understand cultural dynamics at the micro level (the acquisition, variable influence and creative mutation of cultural knowledge) and the macro level (the transmission, diffusion and evolution of cultural practices). Having laid the groundwork for an integrated study of norm—normology, we then introduce the articles of this special issue contributing theoretical refinements and empirical evidence from different methods and levels of analysis. Managerial implications are discussed.